Manufacturer collusion: Strategic implications of the channel structure - Markus Reisinger; Tim Paul Thomes (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We investigate how the structure of the distribution channel affects tacit collusion between manufacturers. When selling through a common retailer, we find - in contrast to the conventional understanding of tacit collusion that firms act to maximize industry profits - that colluding manufacturers strategically induce double marginalization so that retail prices are above the monopoly level. This lowers industry profits but increases the profit share that manufacturers appropriate from the retailer. Comparing common distribution with independent (exclusive) distribution, we show that the latter facilitates collusion. Despite this result, common retailing leads to lower welfare because a common retailer monopolizes the downstream market. For the case of independent retailing, we also demonstrate that contract offers that are observable to the rival retailer are not necessarily beneficial for collusive purposes.
Keywords: 330; tacit collusion; contract observability; common retailing; independent (exclusive) retailing; two-part tariffs; wholesale price contracts